Study of fungal endophytes as resistance inductors for black Sigatoka (Mycosphaerella fijiensis) control in plantain - Barrios Murillo, Miguel A. (2006)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2006